Shocks from the Information Society: Three Documentary Poems on Critical Information Literacy - Schoenfelder, Jon (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire)

(untitled) (Canadian Association of Professional Academic Librarians / Association Canadienne des Bibliothécaires en Enseignement Supérieur, 2025)
Representing changes to social relations in the late twentieth century, the “Information Society” emerged from several global historical developments: political tension between market ideologies and attempts at alternatives; the integration of computer technology across public and private life; and intense specialization within western systems of knowledge fostering skepticism of grand unifying narratives. At different phases of its emergence, information literacy has been proffered as a solution to the Information Society’s many shocks. But despite investments and codification in national curriculums, information literacy has yielded only marginal success over its 50-year history, neither preventing the worst of the Information Society’s calamities nor achieving its visions of progress. Following modes of documentary poetry and research poetry, these three poems ("Zurkowski's Prism," "The Amazing Dissolving Student," and "A Decade and Another and Another") draw from textual materials of the Information Society and its complex discourses to raise provocative questions about the world which critical information literacy practitioners must face such that they may change it. Each poem traces aspects of its history, its material conditions, and attempts through critical information literacy (both the incomplete and the ongoing) to struggle with its many contradictions.